The Role of Management Intervention towards Enterprise Social Network Adoption - Salim, Siti Aisyah; Othman, Nurul Suraya (Research in Management of Technology and Business, 2021)
Enterprise Social Network (ESN) is an important platform for organizations to communicate, interact, collaborate, and share information. While management intervention is one of the factors that influence employees towards ESN adoption in organizations. Though there are several studies have discussed factors that influence ESN adoption in organization, only few studies have looked into management intervention in specific. Thus, this study aims to examine the level of management intervention towards ESN adoption as well to observe, the relationship between management intervention and ESN adoption. This study used motivation behavior theory to examine this relationship. This study has surveyed 80 respondents from employees in manufacturing industries at Batu Pahat. The sample was collected based on quantitative research method where self-administrated questionnaire and online survey has been applied. The data were analyzed by using Statistical Package for Social Science (SPSS) software to investigate the information of demographic, variables and the relationship between management interventions and ESN intention of adoption. From the analysis, it showed that the level of fulfilment dimension towards ESN adoption has high level. All variables toward intention of adoption show positive significant relationship towards ESN intention of adoption with correlation coefficient of 0.523.